2011
DOI: 10.1002/adma.201103177
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Small Molecule Bulk Heterojunction Solar Cells with High Fill Factors via Pyrene‐Directed Molecular Self‐Assembly

Abstract: Efficient organic photovoltaic (OPV) materials are constructed by attaching completely planar, symmetric end-groups to donor-acceptor electroactive small molecules. Appending C2-pyrene as the small molecule end-group to a diketopyrrolopyrrole core leads to materials with a tight, aligned crystal packing and favorable morphology dictated by π-π interactions, resulting in high power conversion efficiencies and high fill factors. The use of end-groups to direct molecular self-assembly is an effective strategy for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
208
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(214 citation statements)
references
References 41 publications
5
208
0
Order By: Relevance
“…An example is given by the seminal work of Lee et al, who added planar conjugated moieties on opposite sides of molecular dyes to promote molecular stacking. [5] More recently, the utilization of triazatruxene (TAT) derivatives as planar end-groups grafted on different molecular dyes has been demonstrated by I. Bulut et al [6] Their results suggest that the TAT-dye-TAT architecture allows to strengthen the molecular stacking behavior, while the optical properties remain essentially set by the central dye. Herein, we follow the same strategy to positively alter the self-assembling properties of the TB2 derivative and explore its consequences on OPV device performances.…”
mentioning
confidence: 99%
“…An example is given by the seminal work of Lee et al, who added planar conjugated moieties on opposite sides of molecular dyes to promote molecular stacking. [5] More recently, the utilization of triazatruxene (TAT) derivatives as planar end-groups grafted on different molecular dyes has been demonstrated by I. Bulut et al [6] Their results suggest that the TAT-dye-TAT architecture allows to strengthen the molecular stacking behavior, while the optical properties remain essentially set by the central dye. Herein, we follow the same strategy to positively alter the self-assembling properties of the TB2 derivative and explore its consequences on OPV device performances.…”
mentioning
confidence: 99%
“…The above changes in the film properties upon thermal annealing result in large improvements in J sc and FF and, hence, also in the PCE. 32,33 The inset in Fig. 8 shows the EQE of the best performing device.…”
Section: Resultsmentioning
confidence: 99%
“…(HD/OD)-DPP-A-PY was synthesized according to the pathway shown in Scheme 1, while OD-DPP-PY was synthesized according to the literature procedure [4]. Compound 1 was synthesized through a known procedure [7].…”
Section: Synthesismentioning
confidence: 99%
“…Holmes et al reported a series of liquid crystalline organic donor molecules consisting of hexa-peri-hexabenzocoronene (FHBC) and DPP unit with 1.59% of power conversion efficiencies (PCEs) [3d], and Nguyen et al also reported a donor molecule comprising the benzofuran-substituted DPP with 4.4% of PCEs [3a]. Recently, pyrene-DPP-pyrene triad with thienylene bridging to either 1-or 2-position of pyrene was developed by Frechet et al to show high PCEs: over 4% PCEs was obtained for 2-pyrene triad while only 0.7% PCE was obtained for 1-pyrene triad [4]. However, it should be noted that the 2-pyrene derivatives require much more demanding synthesis than that of 1-pyrene derivatives due to the different reactivity of 1-and 2-positions of pyrene, i.e.…”
Section: Introductionmentioning
confidence: 96%